Diagnosis of Chlamydia trachomatis infections in asymptomatic men and women by PCR assay. - Toye, B (1996)
A PCR assay was evaluated for its ability to detect genital chlamydial infection in asymptomatic men and women. Urethral swab specimens were collected from 472 men for culture and PCR assay, and first-void urine (FVU) specimens were collected from 379 of these men for enzyme immunoassay (EIA) and PCR assay. Cervical swab specimens were collected from 242 women for culture, EIA, and PCR assay. Patients were considered infected if they were culture positive or positive by PCR with both plasmid- and major outer membrane protein-based primers. By using this extended "gold standard," the prevalence of infection in this population was 7.6% for men and 7.9% for women. For men, the sensitivities of urethral swab specimen culture and PCR and FVU specimen EIA and PCR were 61, 72, 55, and 91%, respectively. All assays had specificities of > or = 99.8%. The positive and negative predictive values for PCR testing of FVU specimens were 100 and 99.4%, respectively, compared with values of 96.3 and 97.8%, respectively, for PCR of urethral swab specimens. The sensitivities of cervical swab specimen culture and PCR testing were 42 and 90%, respectively, with corresponding specificities of 100 and 99.3%. All cervical swabs were negative by EIA. Molecular techniques such as PCR assays are valuable tools for the detection of symptomatic genital chlamydial infection. In particular, PCR assays of FVU specimens from men offer a highly sensitive, noninvasive screening tool that will likely improve patient compliance for diagnostic testing.